Studi Analisis Kebutuhan Pembelajaran pada Virtual Lab Mata Kuliah Microteaching untuk Peningkatan Keterampilan Mengajar - Aswan, Dedy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the learning needs in the Virtual Lab for the Microteaching course to enhance the teaching skills of students. The research method employed is a qualitative approach, with data collected through online questionnaires and qualitative surveys. The respondents consist of 20-30 students enrolled in the Microteaching course at Universitas Negeri Makassar. The results indicate that before using the Virtual Lab, the majority of students felt unprepared and lacked confidence in their teaching abilities. However, after participating in training using the Virtual Lab, they reported significant improvements in understanding learning concepts, confidence in designing learning activities, and readiness to face unexpected situations in the classroom. Respondents provided positive assessments of the interface and features of the Virtual Lab, although some experienced difficulties in operating certain features. The interactive and high-quality learning media used in the Virtual Lab proved effective in enhancing student motivation and engagement. Additionally, the constructive feedback received after teaching simulations contributed to the improvement of teaching skills and increased motivation to continue learning. This study emphasizes the importance of integrating technology in education to improve teaching quality and prepare future teachers to face real-world challenges. Recommendations are provided for the development of training on the use of the Virtual Lab and the enhancement of feedback systems to support the effectiveness of teacher training in the future.